2008
DOI: 10.1002/lpor.200810010
|View full text |Cite
|
Sign up to set email alerts
|

Fibre gratings and devices for sensors and lasers

Abstract: Although mainstream grating writing, more often than not using single photon excitation of germanosilicate based defects with CW 244 nm light, remains the key technology for complex devices it is now being complemented by a whole host of processes which can enhance and tailor the properties of both conventional and not-so-conventional fibre Bragg gratings. Further, processes for writing of gratings in non-germanosilicate fibres have also continued to develop and include multi-photon excitation directly into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
162
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(163 citation statements)
references
References 78 publications
(98 reference statements)
0
162
0
1
Order By: Relevance
“…For a general review on photosensitivity and grating types, see [Canning 2008a]. Another variant with superior high temperature stability is the so-called "chemical composition grating (CCG)" [Fokine 2002] where a periodic index modulation can be regenerated after erasure of the UV induced type-I grating written in H-loaded germanosilicate fibre, which happens to contain fluorine, if annealed ~1000°C.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…For a general review on photosensitivity and grating types, see [Canning 2008a]. Another variant with superior high temperature stability is the so-called "chemical composition grating (CCG)" [Fokine 2002] where a periodic index modulation can be regenerated after erasure of the UV induced type-I grating written in H-loaded germanosilicate fibre, which happens to contain fluorine, if annealed ~1000°C.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Gratings are now readily written into both photosensitive and non-photosensitive structured optical fibers of various sorts using a range of photosensitive mechanism -a specific review of these mechanisms can be found elsewhere [35]. Figure 4 shows the type of fibers into which gratings have been successfully written.…”
Section: Discussionmentioning
confidence: 99%
“…Type II gratings are modifications above the damage threshold of the host material. The most recent addition are Type R gratings that form out of annealed Type I gratings after prolonged heating [81].…”
Section: Grating Classificationmentioning
confidence: 99%